Comparative study on complications of screws versus plates for comminuted radial head and neck fractures with two or three fragments - Fu, Yuliang; Cao, Yuan; Cui, Zengzhen; Bai, Liangyu; Norman Pan, Xiaoyu; Lv, Yang (Frontiers in Surgery, 2026)
BackgroundThis retrospective study aimed to compare the efficacy of internal fixation using headless compression screws (HCS) and radial head locking plate (RLP) for comminuted radial head and neck fractures with no more than 3 displaced fragments.MethodsThis retrospective study included 84 patients with radial head and neck fractures treated at Peking University Third Hospital between January 2013 and December 2022, with 38 and 46 patients in the HCS and RLP groups, respectively. The main outcome was the comparison of complications between the two groups. Demographic data, pre-operative time (POT), operation time (OT), and hospital stay time (HST) were also recorded. The Mayo Elbow Performance Score (MEPS), range of movement of the elbow and forearm, and reasons for re-operation were compared between the two groups.ResultsAll patients were followed up for an average of 66.4 months (range, 20–135 months). One patient in each group underwent radial head replacement due to non-union, while the remaining patients achieved bone union. There was no statistically significant difference in the clinical outcomes between the two groups (p > 0.0023). Additionally, the re-operation rate due to symptomatic hardware was significantly higher in the RLP group (28.3%) than that in the HCS group (2.6%, p = 0.002).ConclusionFor internal fixation of comminuted radial head and neck fractures with no more than three displaced fragments, both HCS and RLP achieved good outcomes. However, the RLP increased the incidence of complications and re-operation associated with internal fixation compared to HCS.